2022
DOI: 10.1002/jemt.24249
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the antifungal efficacy of sodium hypochlorite, chlorhexidine, and silver nanoparticles against Candida albicans

Abstract: Candida albicans is a microorganism that causes root canal infections. However, it cannot be eliminated with conventional irrigation solutions. Recently, silver nanoparticles (AgNPs) have become popular for their superior antimicrobial effects. The purpose of this study was to evaluate the antifungal effect of AgNPs to C. albicans comparing with 5.25% sodium hypochlorite (NaOCl) and 2% chlorhexidine (CHX). Silver nanoparticles were synthesized by chemical reduction method. Minimum inhibitory concentration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The literature reported that silver acts in Candida spp. by disrupting its external layer, altering membrane permeability and some normal intracellular functions (e.g., silver ions interact with the thiol groups of enzymes and proteins, and bind DNA); here, we indirectly demonstrated these activities [ 24 , 25 , 26 , 27 ]. In fact, as shown by the FESEM micrographs, the yeasts’ morphology was altered by the silver’s presence in the 3D scaffolds since filamentous forms were observed instead of the physiological oval shape.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The literature reported that silver acts in Candida spp. by disrupting its external layer, altering membrane permeability and some normal intracellular functions (e.g., silver ions interact with the thiol groups of enzymes and proteins, and bind DNA); here, we indirectly demonstrated these activities [ 24 , 25 , 26 , 27 ]. In fact, as shown by the FESEM micrographs, the yeasts’ morphology was altered by the silver’s presence in the 3D scaffolds since filamentous forms were observed instead of the physiological oval shape.…”
Section: Resultsmentioning
confidence: 77%
“…In full agreement with our results, the Vazquez-Munoz research group assessed the antimicrobial activity of silver nanoparticles (AgNPs) on C. auris planktonic and biofilm growth phases; they revealed an alteration to the usual C. auris shape, with elongated forms [ 51 ]. Additionally, other authors demonstrated the anti- C. albicans and anti- C. auris effects of AgNPs [ 25 , 26 , 52 , 53 , 54 ]. Mare A.D. and colleagues (2021), when analyzing AgNPs mediated by spruce bark extract (SBE), demonstrated their antifungal activity and inhibited biofilm production for C. albicans , C. auris , and C. guilliermondii [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, chlorhexidine exhibits biocidal activity against Gram-positive bacteria, and, if the minimum inhibitory concentration (MIC) is maintained, it can also inhibit Gram-negative bacteria. Additionally, chlorhexidine remains active against DNA and RNA viruses and yeast, including Candida albicans [48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Several oral conditions were reported in COVID-19 patients, including fungal infections like oral thrush (oral candidiasis), particularly among those who already had a predisposing condition, and were treated with antibiotics [ 3 ]. Furthermore, Candida spp., especially Candida albicans , have a role in primary and secondary endodontic infections, acting as co-pathogens with bacteria [ 4 ], and in periodontal infections [ 5 ], in which sodium hypochlorite and chlorhexidine solution have limited antifungal activity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%